Valor na lógica dominante do serviço - Gonçalves, Gabriel Freitas (2019)
This work aimed to analyze, from the perspective of the Service-dominant logic, the perspective of value in education. The Service-dominant logic works with an integrative perspective of services in all economic aspects, proposing a way of understanding the relations established among the actors in value cocreation. The theoretical framework allowed a vision of the evolution of this theory and how the perception of value is empirically studied, which provided the basis for the construction of the data collection instrument and the categories of analysis. Four focal groups were used to collect data with the aid of a semi-structured script, which was analyzed through content analysis. This procedure led to the construction of 17 initial categories that converged to three, being: Value creation; Adding value; and Individual as resource that relate to some of the axioms of the Service-dominant logic, which provides empirical evidence for this theoretical construction. At the end of the study, it is perceived that value is a dynamic and complex process, surrounded by actors that influence directly or indirectly the perception of value.